(untitled) (Journal of the College of Education for Women, 2019)
Has influenced technology contact on social values in the Arab community in general andthe Iraqi community in particular whether this positive change or a negative effect on the levelof the individual and society is reflected this influence through socialization and humanrelations as well as the behavior of individuals and dealing with others, where the world wasto soon pass changes slow, and the amounts that can be measured and trends can be calculatedand the effect of points can be identified and controlled, but the technological changes andopenness cognitive features that seemed evident in the last decade of the twentieth centurybrought about a change in all scales and distances traditional considerations.